Explicit Teaching of Academic Vocabulary in EFL: Preparing Icelandic students for education at university level - María Pétursdóttir 1973- (2013)
The focus of this study was to develop a program to teach academic vocabulary to upper-secondary students of English in Iceland, and to evaluate the success of the material used. The academic words targeted were chosen from the Academic Word List (Coxhead, 2000). Knowledge of the lexis was measured before and after instruction and the increase in knowledge of a study group that received explicit instruction was then compared to control groups that did not. While a pre-test revealed a lack of receptive knowledge of academic vocabulary among the students, it reported an even greater lack of productive knowledge. The students in the two control groups did not receive instruction of the target vocabulary although one group was exposed to the lexis through reading material. Neither control group displayed gain in knowledge of the target vocabulary while the students who underwent the treatment showed significant improvement, both in receptive- and productive knowledge of the target words. The study also showed that while words within each sublist of the AWL are equally frequent in academic texts, they have a lower frequency in general language. Therefore, some words on the AWL are more important to teach than others and these can be predicted by their frequency in general. Keywords: academic vocabulary, explicit vocabulary teaching, incidental vocabulary learning, receptive vs. productive vocabulary.